A qualitative study to explore the lived experiences of people who are tilted ‘wubao’ within ‘three no’s’ category in government-funded care homes in China - Xiangping Fan; Rong Ding; Xiubin Zhang (BMC Geriatrics)
Abstract Background There are limited studies explored the lived experience of older people without children who titled ‘Wubao’ in China. This study aims to understand the lived experience of the older people who titled ‘Wubao’ and fit in the ‘Three No’s’ category in government-funded care homes in China. Methods The phenomenological qualitative approach was used for this study. Thematic analysis was used for data analysis. Findings Three main themes and six subthemes were identified. Theme 1: It has significantly changed basic life needs (availability of physical life resources; availability of basic medical care). Theme 2: Lack of personal-centered care services (lack of specialized dietary needs; lack of care equipment to support personal needs). Theme 3: Social attitude of living in government funded care homes (losing social connections; perceiving social stigma). Conclusions The findings highlighted that the government-funded care home is important to support and meet the basic physical needs for this group population. However, the personalized needs seem to be underestimated in this type of care home. It suggests that this type of care home should pay more attention to the older people’s emotional needs, and the government should consider how to ensure social inclusivity for them.